2012
DOI: 10.3109/0284186x.2012.682629
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of combined chemotherapy with irinotecan and S-1 (IRIS) plus bevacizumab in patients with inoperable recurrent or advanced colorectal cancer

Abstract: Background. In Japan, a study comparing the effectiveness and safety of irinotecan plus S-1 (IRIS) with those of a combination of 5-fluorouracil, leucovorin, and irinotecan (FOLFIRI) as second-line treatment in patients with advanced or recurrent colorectal cancer demonstrated that IRIS was non-inferior to FOLFIRI. We previously reported that IRIS is also effective as first-line treatment. Patients and Methods. Eligibility criteria included inoperable recurrent colorectal cancer with a confirmed diagnosis of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…In our study, the administered dose of irinotecan was lower. However, recent studies have reported good outcomes with oral S-1 and irinotecan plus bevacizumab, used instead of FOLFIRI plus bevacizumab, in patients with MCRC who had not previously received chemotherapy [30,31,32]. The effectiveness of combination chemotherapy with S-1, irinotecan, and bevacizumab in our study was consistent with the findings of previous studies.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In our study, the administered dose of irinotecan was lower. However, recent studies have reported good outcomes with oral S-1 and irinotecan plus bevacizumab, used instead of FOLFIRI plus bevacizumab, in patients with MCRC who had not previously received chemotherapy [30,31,32]. The effectiveness of combination chemotherapy with S-1, irinotecan, and bevacizumab in our study was consistent with the findings of previous studies.…”
Section: Discussionsupporting
confidence: 83%
“…In previous studies, irinotecan was administered in the following doses: 100 mg/m 2 biweekly by Komatsu et al [30], 80 mg/m 2 biweekly by Mizushima et al [32], and 150 mg/m 2 triweekly by Yamada et al [31]. In all of these studies, irinotecan was given as a 90-min infusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations